Changing trends in the management of intertrochanteric hip fractures – A single centre experience. Issue 7 (July 2016) - Page, Piers R.J.; Lord, Roxana; Jawad, Ahsin; Dawe, Edward; Stott, Philip; Rogers, Benedict; Gill, Richie
Abstract: With an annual incidence greater than 65, 000 in the United Kingdom, hip fractures are a common but debilitating injury predominantly affecting those over 65. Treatment is based on the anatomical location of the fracture relative to the capsule of the hip joint – fractures occurring within it are treated by arthroplasty, while extracapsular fractures are an indication for fixation. Intertrochanteric fractures are further grouped as stable (AO/OTA 31A1/A2) or unstable (31A3) which in turn governs in the current UK guidelines whether this fixation is achieved with a dynamic hip screw or intramedullary device. Anecdotally, some units are tending towards intramedullary devices for 31A2 fractures as well, a practice which from the evidence does not appear to confer benefit and carries an excess cost. We reviewed our data submitted to the National Hip Fracture Database over the last five years and identified all intertrochanteric fractures, from which cohort we identified all patients with 31A2 fractures by review of radiographs. The cohort comprised 370 patients. We then recorded age, gender, ASA grade, abbreviated mental test score, residence from where admitted, length of stay, destination on discharge and whether any further operations were required. There was no significant difference in the demographics of the groups, year-on-year, except gender mix. There was a significant, twenty-fold rise in the use of intramedullary devices between 2011 and 2015. Length of stay, length of overall episode of care, revision rates, mortality and destination on discharge were unchanged. This use is not supported by NICE guidelines and this study offers no evidence to contradict this position. We advocate all centres examine their practice to avoid a costly intervention without clinical benefit.